Sex and the city - Ellis, Antonia, 1963-; Raab, Jane.; King, Michael Patrick, 1954-; Chupack, Cindy; Parker, Sarah Jessica; Cattrall, Kim.; Davis, Kristin, 1966-; Nixon, Cynthia; Thomas, John.; Berenbaum, Michael, 1962-; Lieberstein, Dan.; Field, Patricia; et al. (New York, NY : HBO Video, 2004)
Sex columnist Carrie and her gal pals Charlotte, Miranda, and Samantha continue on their sexual conquests. Carrie believes things are on an upswing because of her hot date with Jack, while Charlotte is upset over Harry's disclosure that he would never marry a non-Jew. This leads to her decision to convert to Judaism. Samantha feasts her eyes on Jerry, the man who soon becomes her boyfriend. Charlotte hears the words she's been longing for from Harry. Miranda continues to emotionally distance herself from Steve. A visit from Mr. Big forces Carrie to re-think their relationship one last time.
To market, to market -- Great sexpectations -- The perfect present -- Pick-a-little, talk-a-little -- Lights, camera, relationship -- Hop, skip, and a week -- The post-it always sticks twice -- The catch -- A woman's right to shoes -- Boy, interrupted -- The domino effect -- The one.
Originally aired on television during the 2003 season.
Based on the characters created by Darren Star and based on the book by Candace Bushnell.
Special features: audio commentaries by executive producer Michael Patrick King; a panel discussion filmed at The Museum of Television & Radio Seminar featruing the cast and crew.
Director of photography, John Thomas ; art director, Anna Louizos ; editor, Michael Berenbaum ; music supervisor, Dan Lieberstein ; costume designers, Patricia Field, Molly Rogers ; production designer, Jeremy Conway.
Sarah Jessica Parker, Kim Cattrall, Kristin Davis, Cynthia Nixon.
MPAA rating: Not rated.
Keywords: Women -- Sexual behavior -- Drama; Journalists -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama; Sex customs -- New York (State) -- New York -- Drama; Television comedies; Video recordings for the hearing impaired